Implementation of the OPOP Program in Economic Development and Entrepreneurship in Islamic Boarding Schools - Dyana Maftuhatu Rosyidah; Cepi Safruddin Abd. Jabar; Lilin Rofiqotul Ilmi; Fauziah Yolviansyah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The One Pesantren One Product (OPOP) program implemented at Pondok Pesantren Darul Falah Sukorejo aims to empower the pesantren’s economy and foster entrepreneurship among students by developing and marketing unique products. This study employs a qualitative case study approach to assess the implementation and impact of the OPOP program at the pesantren, focusing on the production and marketing of Beras Pink (Pink Rice). Data were collected through semi-structured interviews, participatory observation, and document analysis. The results reveal that while the pesantren has made notable progress in product development and marketing, it still faces challenges such as limited production capacity, difficulty accessing broader markets, and a lack of digital marketing expertise. The absence of a well-trained managerial team hampers the ability to scale the business, and although community participation is strong, the higher pricing of the products compared to similar market offerings remains a barrier to wider market acceptance. The study emphasizes the need to strengthen managerial and digital marketing skills to fully leverage the potential of the OPOP program. These findings highlight the critical role of entrepreneurial education in pesantren, providing valuable insights into how OPOP can be optimized to empower pesantren communities, ensuring sustainability and broader impact in other pesantren contexts